Confronting political Islam : six lessons from the west's past - Owen, John M. (John Malloy), 1962- (Princeton University Press, 2015)
How should the Western world today respond to the challenges of political Islam? Taking an original approach to answer this question, Confronting Political Islam compares Islamism's struggle with secularism to other prolonged ideological clashes in Western history. By examining the past conflicts that have torn Europe and the Americas-and how they have been supported by underground networks, fomented radicalism and revolution, and triggered foreign interventions and international conflicts-John Owen draws six major lessons to demonstrate that much of what we think about political Islam is wro.